Copper(I)-catalyzed direct C-H trifluoromethylation of imidazoheterocycles with Togni's reagent. Issue 8 (21st February 2019) - Wang, Ruonan; Wang, Jingcai; Tang, Qingxuan; Zhao, Xin; Wang, Junfeng; Leng, Yuting; Wu, Yangjie; Chang, Junbiao; Wu, Yusheng; Zhang, Zhaoda; Wang, Shiwei
Graphical abstract: Highlights: Cu(I)-catalyzed trifluoromethylation of imidazoheterocycles with Togni's reagent. Simple imidazoheterocycles to trifluoromethylation product at room condition. Clean reaction, ease of product isolation and a simple experimental procedure. Abstract: A mild and efficient trifluoromethylation of imidazopyridines with Togni's reagent in the presence of inexpensive base has been realized at room temperature. This methodology has several advantages: (1) using efficient copper(I) as catalyst and inexpensive K3 PO4 as base, (2) no additional oxidants required for this reaction. (3) good functional group tolerance. An array of trifluoromethylated imidazopyridines with broad functionalities were obtained in acceptable yields.